Systematic Literature Review: Manifestasi Metode Regulatory Impact Analysis (RIA) Pada UU No. 17 Tahun 2023 Tentang Kesehatan - Khasanofa, Auliya; Khariri, Agus Al (Jurnal Ilmiah Penegakan Hukum, 2024)
The research aims to find out the main essence of RIA as an assessment tool for laws and regulations in Indonesia, especially regulations related to the Health Law. When viewed based on previous reviews, it is clear that in the process of forming laws and regulations in Indonesia, improvements are needed to the codification stage. This is done so that the legal products issued can apply efficiently. In the scope of the health world, Law Number 17 of 2023 concerning Health has attracted a lot of analytical attention because it introduces new guidelines to the health regulation system. The research method used is normative legal research with an analytical descriptive approach which is then analyzed qualitatively. The results of the study show that to regulate the authority and responsibilities of health workers, improve the quality of health services, including providing protection to the community. Currently, the law-making process focuses more on compiling legal texts that comply with legal provisions, with a focus on conformity and compliance with higher regulations. This often ignores other aspects that are also important. Therefore, the Regulatory Impact Analysis (RIA) method is important for policy makers to assess how much the costs are compared to the benefits of the regulations made.